CREATING A MODERATION VILLAGE BASED ON RECOGNITIVE LEARNING IN LEMBAR DISTRICT - Agus Dedi Putrawan (Tahiro : Journal of Peace and Religious Mederation, 2024)
The existence of an international port in Lembar District, West Lombok Regency, confirms the global village where all forms of foreign culture and variants will be easy to access.influenceattitudes and behavior of society that reflect a multicultural society. In addition, identity politics during general elections always threatens divisions between religious communities and diverse cultures in Lembar District. Borrowing the theory and concept of the encounter school to see the phenomenon of reconstruction and rehabilitation of the post-conflict social system in Mareje Village, Lembar District. This research was conducted because of the uniqueness of the existence of various tribes and religions in Lembar District, which are immigrant communities. There are three religions (Islam, Hinduism and Buddhism) that inhabit 10 villages, and there are Sasak, Javanese, Samawa, Mbojo and Balinese tribes in Lembar District.